2018
DOI: 10.1159/000495368
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoside Protects Against Pressure Overload-Induced Cardiac Remodeling via the AKT Signaling Pathway

Abstract: Background/Aims: Cardiac hypertrophy is a major predisposing factor for heart failure and sudden cardiac death. Hyperoside (Hyp), a flavonoid isolated from Rhododendron ponticum L., is a primary component of Chinese traditional patent medicines. Numerous studies have shown that Hyp exerts marked anti-viral, anti-inflammatory, anti-oxidant, anti-cancer, anti-ischemic, and particularly cardio-protective effects. However, the effects of Hyp on cardiac hypertrophy have not been explored. The aims of this study wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 35 publications
(42 reference statements)
0
17
0
Order By: Relevance
“…CMs were obtained [30] by using previously published methods. Immunofluorescence staining showed that the CMs expressed cTnT (Figure 1(a)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CMs were obtained [30] by using previously published methods. Immunofluorescence staining showed that the CMs expressed cTnT (Figure 1(a)).…”
Section: Resultsmentioning
confidence: 99%
“…Primary cultures of neonatal mouse CMs were prepared as previously described [30] with minor modifications. Briefly, 1- to 2-day-old mice were euthanized after performing heparinization for 5-10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Among them, hyperoside prevents ageassociated renal injury through inhibition of autophagic activity by mammalian target of rapamycin (mTOR)-independent and AMPK-autophagy activating kinase 1 (ULK1) signaling pathways. 31) Moreover, hyperoside improves cardiac function and prevents the development of cardiac hypertrophy, 32) suggesting that STH_KP17001 may suppress VCD-induced cardiac hypertrophy via hyperoside-induced AMPK inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Hyp was found to have a protective effect on chronic liver fibrosis induced through carbon tetrachloride (Zou et al, 2017). Moreover, Hyp could protect against cardiac remodeling induced by pressure overload through the inhibition of AKT signaling (Wang et al, 2018). In the present study, we explored the protective effects of Hyp on Blm-induced pulmonary fibrosis in a C57BL/6 mice model.…”
Section: Introductionmentioning
confidence: 94%